Policy Implementation of Restricting Community Activities (PPKM) Micro As An Effort To Control The Spread of Covid-19 In Pulang Pisau District - Syahid Kamal Firdaus; Andi Tenri Sompa; Siswanto Rawali (International Journal of Politic, Public Policy and Environmental Issues, 2022)
The purpose of this study was to analyze the Implementation of the Policy for Enforcing Micro Community Activity Restrictions (PPKM) in the Kalawa Sub-District, which was carried out by the PPKM Micro Command Post Team in the Kalawa Village and to analyze the factors that became obstacles to the Implementation of the Enforcement of Micro Community Activity Restrictions (PPKM) in the Kalawa Village, Pulang Pisau Regency. The method used in this research is descriptive qualitative. Data collection techniques through triangulation. The data analysis technique used is Miles and Huberman's interactive data analysis. Based on the results of this study, shows that the implementation of the micro PPKM policy to control the spread of covid-19 in the Kalawa Village is quite good in terms of 3M activities (wearing masks, washing hands, and maintaining distance), 3T (Testing, Tracing and Follow Up) and vaccination. Based on the influencing factors, it shows that the communication of information distribution is going well and consistently so that the community feels the impact of the policy. Human resources are sufficient and involve various elements of society, budgetary resources are sufficient, and equipment resources also meet the needs and resources for authority for the micro PPKM team to facilitate immediate decision-making. There are still policy implementers who do not have the commitment and are not responsible even though they have been given sufficient incentives. The formation of the organizational structure following the rules and the implementation of the activities of the micro PPKM team is well coordinated.